Socialinė teorija kintančiame pasaulyje: kelyje į dinaminę socialumo koncepciją? - Furs, Vladimir (Problemos, 2004)
Social-theoretical thought displays in the seventies-nineties a tendency to transcend the ’strong conception of society’. That conception crystallized in the context of European nationalism and gained its axiomatic character in the ’Fordist age’. It implies a set of the interconnected presuppositions: (1) ’societalism’, i.e., the idea that ’society’ as all-sufficient macrosocial unit is the fundamental frame of total social life; (2) the idea of evolutionary transition (through differentiation) from ’Gemeinschaft’ to ’Gesellschaft’; (3) naturalization of the Western experience of ’modemity’. The conceptual innovations, represented successively in theory of practices (Bourdieu, Giddens), in social postmodemism (Baudrillard, Maffesoli), and in globalization theory (Beck, Giddens, Robertson), mark the stages of the onward revision and disavowal of the ingredients of the ’strong conception of society’. A ’dynamic conception of the social’ is suggested hypothetically as the terminal and integrating point of that tendency